Pengaruh Bauran Pemasaran terhadap Minat Berkunjung Wisatawan ke Destinasi Agrowisata di Cibodas, Kecamatan Lembang, Kabupaten Bandung Barat - Badriyatul Huda; Adi Indradi Wazdi (Jurnal Maps (Manajemen Perbankan Syariah), 2023)
Agro-tourism can be an alternative option in increasing income for farmers without reducing the importance of the agricultural sector in building food security in various countries, including Indonesia. However, the potential for agro-tourism has not been properly explored, so that the number of visits is still less compared to other tourist objects. The purpose of this study was to examine the effect of the marketing mix consisting of product, price, promotion, and place on the interest of tourists to visit agro-tourism destinations. In this case the object is agro-tourism in Cibodas Village, Lembang District, West Bandung Regency. For data analysis, the researchers used a structural equation model (SEM) with the help of the WarpPLS application. The expected result is a model of the influence of the marketing mix on tourist interest in visiting agro-tourism objects in Cibodas Village, Lembang District, West Bandung Regency. The results showed that prices, promotions, and places had a positive and significant effect on interest in visiting agrotourism destinations in Cibodas Village